224k views
0 votes
If f(x) = 2x + 2 and g(x) = x2 - 1, find (f - g)(x).

2 Answers

5 votes

Answer:

-x2+2x+3

Explanation:

(2x+2)- (x2-1)

2x+2-x2+1

-x2+2x+3

User Wing
by
4.6k points
4 votes

Answer:

(f - g)(x) = - x² + 2x + 3

Explanation:

f(x) = 2x + 2

g(x) = x² - 1

To find (f - g)(x) subtract g(x) from f(x)

That's

(f - g)(x) = 2x + 2 - [ x² - 1]

(f - g)(x) = 2x + 2 - x² + 1

Group like terms

That's

(f - g)(x) = - x² + 2x + 2 + 1

We have the final answer as

(f - g)(x) = - x² + 2x + 3

Hope this helps you

User Fudgey
by
4.4k points